2020
DOI: 10.5664/jcsm.8686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous positive airway pressure on maximal exercise capacity in patients with obstructive sleep apnea: a systematic review and meta-analysis

Abstract: Study Objectives: Exercise capacity is impaired in obstructive sleep apnea (OSA). There are conflicting reports on the effect of continuous positive airway pressure (CPAP) on maximal exercise capacity. The objective of this review was to determine if there is a change in exercise capacity and anaerobic threshold following CPAP treatment in OSA patients. Methods: We conducted a systematic review and meta-analyses to summarize the changes in peak rate of oxygen uptake (V Ȯ2 peak) or maximum rate of oxygen uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…While other studies in patients with simple HF or simple OSA show opposite conclusions. [50][51][52] This may be due to OSA limiting the patient's ability to exercise 53 or HF limiting the patient's ability to use oxygen. 54 About this, one of the included studies inspired us that exercise may do good to this type of comorbidity, 29 since aerobic exercise also appears in the F I G U R E 5 Subgroup analysis of PAP efficacy to cardiac function in participants comorbid with HF and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies in patients with simple HF or simple OSA show opposite conclusions. [50][51][52] This may be due to OSA limiting the patient's ability to exercise 53 or HF limiting the patient's ability to use oxygen. 54 About this, one of the included studies inspired us that exercise may do good to this type of comorbidity, 29 since aerobic exercise also appears in the F I G U R E 5 Subgroup analysis of PAP efficacy to cardiac function in participants comorbid with HF and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous CPAP treatment effect on aerobic capacity in patients with OSA has been already described [ 2 ]. In fact, CPAP therapy for at least eight consecutive weeks was predominantly associated with significant improvements in VO 2 max [ 8 , 9 , 20 , 21 ]. CPAP therapy may normalize gas exchanges during sleep and contribute to structural and bio-energetic changes in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown reduced maximal aerobic exercise capacity in patients with OSA compared to control subjects [ 6 , 7 ]. Previous studies showed improvements in cardiac function and cardiorespiratory fitness in patients with OSA after eight weeks of nasal continuous positive airway pressure (CPAP) treatment [ 8 , 9 ]. Indeed, nasal CPAP is the gold-standard treatment for moderate to severe OSA and has been proven to reduce cardiovascular mortality and non-fatal cardiovascular events in this population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various comorbidities, OSA patients often experience muscle fatigue and reduced physical performance [ 7 ] resulting in limited daily activities and quality of life. In fact, recent meta-analyses showed that maximum oxygen uptake (aerobic capacity) under cycle ergometer test conditions is significantly reduced in patients with (severe) OSAS [ 8 , 9 ] compared to healthy controls and may be improved by continuous-positive-airway-pressure (CPAP) therapy [ 10 ]. The limiting factors of O 2 transport or muscle function responsible for an inverse relation between AHI and aerobic capacity have yet remained unclear, but may not include histomorphological muscle microvascularization, which was found to be increased at least in the tibialis anterior muscle [ 11 ].…”
Section: Introductionmentioning
confidence: 99%